Temporal and geographical patterns of nitazene detections in drug samples and biospecimens in the United States, 2019–2024. - Zhu, David T.; Fitzgerald, Nicole D.; Palamar, Joseph J.; Krotulski, Alex J. (Addiction, 2026)
Background and aims: Nitazenes are a novel subclass of synthetic opioids that have been increasingly implicated in the United States (US) overdose crisis. Despite their growing presence in the illicit drug supply, national trends have not been systematically evaluated. This study aimed to describe temporal and geographic patterns in nitazene detections and assess substances co‐involved in nitazene‐positive biospecimens. Design: Cross‐sectional study using forensic data from two national sources: the US Drug Enforcement Administration's National Forensic Laboratory Information System (NFLIS) and the Center for Forensic Science Research & Education's (CFSRE) NPS Discovery Program. Setting and cases: Nitazene detections in all 50 US states and the District of Columbia between 2019 and 2024. Measurements We quantified annual nitazene detections overall and by individual nitazene analog, US Census region and state. Temporal trends were modeled using piecewise linear regression with a Poisson distribution and log link, nationally and by region. NPS Discovery data were used to characterize substances co‐involved with nitazene‐positive biospecimens. Findings Between 2019 and 2024, 7117 nitazene analog reports were submitted to NFLIS, increasing from 43 in 2019 to 1905 in 2024. Counts rose sharply from 2019 to 2021 [count ratio = 7.32; 95% confidence interval (CI) = 2.22–24.20] but did not increase statistically significantly from 2021 to 2024 (count ratio = 1.08; 95% CI = 1.00–1.17). Early detections were predominated by isotonitazene (97.7% of NFLIS nitazene reports in 2019) but later shifted toward metonitazene and protonitazene (29.5% and 30.1%, respectively, in 2024). NPS Discovery identified 361 nitazene‐positive biospecimens, increasing from 11 in 2019 to 113 in 2024, with counts increasing by approximately 45% per year (count ratio = 1.45; 95% CI = 1.23–1.71). Nearly all nitazene‐positive biospecimens (98.3%) had at least one co‐detected substance, most commonly fentanyl (54.6%). Conclusions: Nitazene detections increased sharply across the United States between 2019 and 2024, with shifting patterns in the prevalence of individual nitazenes and extensive polysubstance involvement. These findings highlight the need to strengthen drug testing capacity, expand epidemiological surveillance and implement targeted public health interventions to mitigate harms associated with this emerging class of synthetic opioids.